(untitled) (American International Journal of Agricultural Studies, 2022)
The study compared nutritional content of four most consumed vegetables [Gnetum africanum Welw, Hensia crinita (Afzel) G.Taylor, Lasianthera africana P.Beauv and Pterocarpus mildbraedii Harms] in Akwa Ibom State, Nigeria. Standard procedures were followed in these assessments: Proximate composition (carbohydrate, protein, fibre, lipid, ash and moisture), Mineral elements (magnesium – Mg, calcium – Ca, iron – Fe, potassium – K and sodium – Na), vitamin C and chlorophyll (a and b). The study showed varied proximate composition, mineral elements, vitamin C and chlorophyll contents across the vegetables assessed. For proximate composition, the following ranges were recorded: 2.78 – 8.99%, 9.63 – 14.00%, 5.43 – 12.15%, 0.001 – 0.013%, 1.91 – 3.14% and 63.38 – 78.01% for carbohydrate, protein, fibre, lipid, ash and moisture contents, respectively. Among the vegetables, G. africanum recorded the highest value for carbohydrate, fibre, lipid, Fe, vitamin C and chlorophyll b. However, recorded the least value for moisture, ash, Mg and K contents. Secondly, L. africana had highest value for moisture, Ca, K, and Na contents and least value for protein, fibre, lipid, vitamin C, chlorophyll a and b contents. The K content in L. africana was statistically different at p≤0.05 with other vegetables. The study recommends the consumption of these nutritious vegetables based on dietary requirement of individuals. JEL Classification Codes: O13.